2018
DOI: 10.1038/s41401-018-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Translational potential of allosteric modulators targeting the cannabinoid CB1 receptor

Abstract: The cannabinoid type-1 (CB 1) receptor, a G-protein-coupled receptor, is an attractive target for drug discovery due to its involvement in many physiological processes. Historically, drug discovery efforts targeting the CB 1 receptor have focused on the development of orthosteric ligands that interact with the active site to which endogenous cannabinoids bind. Research performed over the last several decades has revealed substantial difficulties in translating CB 1 orthosteric ligands into druggable candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…Org27569, ZCZ011, and GAT211 share in common a 2- and 3-alkyl-group-substituted indole ring (indole-2-carboxamides) (Price et al, 2005; Ahn et al, 2012; Cawston et al, 2015; Ignatowska-Jankowska et al, 2015; Laprairie et al, 2017), suggesting this is an important structural requirement for allosteric modulators of CB1R (reviewed in Lu et al, 2018) (Figure 1). CB1R allosteric modulator activity is maintained or improved by C-5 substitution of Org27569 and GAT211 (Cawston et al, 2015; Hurst et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Org27569, ZCZ011, and GAT211 share in common a 2- and 3-alkyl-group-substituted indole ring (indole-2-carboxamides) (Price et al, 2005; Ahn et al, 2012; Cawston et al, 2015; Ignatowska-Jankowska et al, 2015; Laprairie et al, 2017), suggesting this is an important structural requirement for allosteric modulators of CB1R (reviewed in Lu et al, 2018) (Figure 1). CB1R allosteric modulator activity is maintained or improved by C-5 substitution of Org27569 and GAT211 (Cawston et al, 2015; Hurst et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Cawston et al (2015) recently demonstrated that varying the substituents around indole-2-carboxamides can affect the temporal activity of Org27569 derivatives, without affecting the NAM activity these compounds have on CB1R-mediated signaling. Based on the presence of an indole-2-carboxamide, and literature demonstrating the potential actions that might indicate an undocumented CB1R allosteric modulatory activity (Cawston et al, 2015; Lu et al, 2018), we identified indomethacin as a potential allosteric modulator of CB1R.…”
Section: Introductionmentioning
confidence: 99%
“…In the review article entitled "Translational potential of allosteric modulators targeting the cannabinoid CB 1 receptor", the authors discuss recent advances in structural and mechanistic studies on CB 1 R allosteric modulators. They suggest that allosteric CB 1 modulators provide tremendous opportunities to develop CB 1 ligands with novel mechanisms of action; these ligands potentially improve the pharmacological effects and enhance drug safety in treating the disorders by regulating the functions of the CB 1 receptor [6]. In a research article "Identification of novel mouse and rat CB 1 R isoforms and in silico modeling of human CB 1 R for peripheral cannabinoid therapeutics", the authors provide experimental evidence that human CB 1 R has a special isoform in peripheral but not in the CNS (called peripherally enriched CB 1 isoforms), but this feature does not exist in rodents [7].…”
mentioning
confidence: 99%
“…The ligands interacting with CB1R can be classified according to their origin (endocannabinoids, phytocannabinoids, or synthetic cannabimimetics), chemical structure (e.g., indole, urea, or tropane derivatives) and psychoactive (psychotropic and non-psychotropic) effect [41]. Hence, CB1R can be activated by an endocannabinoid agonist such as anandamide (AEA) and 2-arachidonoylglycerol (2-AG), synthetic cannabimimetics (e.g., CP 55,940 and HU-210), or exogenous agonists like ∆-9-tetrahydrocannabinol (THC), a phytocannabinoid responsible for a psychoactive action of marihuana; synthetic inverse agonist/antagonists (e.g., SR-141716A and AM251), and neutral antagonist (e.g., AM6545) [11,15]. All of these aforementioned ligands are orthosteric ligands.…”
Section: Cb1r and Its Ligandsmentioning
confidence: 99%
“…Cannabinoid receptor type 1 (CB1R) is the most abundant GPCR, of the class A receptor, expressed mainly in neurons in the central nervous system [9,10,11]. It is one of the two best-known receptors of the cannabinoids and is an integral part of the endocannabinoid (ECS) system.…”
Section: Introductionmentioning
confidence: 99%